دور نظام الامن الصناعي في تقليل من حوادث العمل من وجهة نظر عمال مستودع عاز البترول المميع نفطال - شعيب محمد أمين; صافي محمد (My University, 2022)
This study aimed to try to identify the extent of the contribution of industrial security to the prevention of work accident injuries by limiting industrial security in this research to two jobs: Training in the field of industrial security as well as the development of preventive awareness methods. In order to address this problem, it is formulated as follows: 1. Do industrial safety measures contribute to the prevention of work accidents for the workers of the Naftal Aflou LPG warehouse? 2. Does training in the field of industrial security contribute to reducing work accidents for workers in the liquid petroleum gas warehouse Naftal Aflou? 3. Do preventive awareness programs in the field of industrial security contribute to raising the level of preventive awareness among the workers of the liquid petroleum gas warehouse Naftal Aflou? And field control. A warehouse for storing and distributing liquid gas bottles in the municipality of Aflou, Laghouat, affiliated with the National Company for Marketing and Distribution of Petroleum Products (Naftal), was chosen through the General Directorate of the LPG region in Tiaret to conduct the field study. The data was gathered and analyzed by developing and distributing a questionnaire to the research community, which included 30 workers who had received industrial security training, as well as conducting interviews with some of the workers and the institution's official of prevention and industrial security, as well as relying on observation and following the steps of the case study approach. It was classified, classified and treated statistically based on percentages to test the hypotheses of the research, and based on the results obtained, which proved the fulfillment of the two procedural hypotheses through which it was confirmed that workers benefit from the training for the contents of the establishment’s industrial safety awareness methods, From work accidents, we can say that workers benefit from industrial security to protect them from Therefore, the general hypothesis has been achieved, and accordingly, a set of recommendations and suggestions have been developed, aimed at reducing workaccident injuries through the functions of industrial security